Pertumbuhan Ekonomi Masyarakat Adat di Wilayah Perkebunan Kelapa Sawit Kabupaten Keerom - Siriwa, Semuel; Silo, Akbar; Tebay, Vince; Torobi, Renida J. (JURNAL EKOLOGI BIROKRASI, 2024)
This article analyzes the impact of the development and expansion of oil palm plantation companies on the socio-cultural and economic transformation of indigenous peoples in Keerom District, Papua Province. The study aims to analyze the changes that have occurred in the social structure, cultural practices, and economic systems of indigenous peoples, as well as identify factors that affect their economic conditions after the entry of oil palm plantations. This article uses qualitative research with a descriptive approach. The study was conducted in villages scattered by oil palm plantations in Keerom District. The research instruments used were recording devices and notebooks. Data collection techniques included in-depth interviews and observation. Data analysis includes the stages of data reduction, data presentation, and conclusion drawing or verification. The results show that the presence of oil palm plantations has resulted in significant erosion of traditional practices and customary land tenure systems. The transformation of the ecological landscape has resulted in the loss of access to natural resources that have been the economic and spiritual basis of the community. The shift from a subsistence economy to a wage-based economy has changed social dynamics and family structures.